O processo projetual do design de interiores e a integração dos princípios da sustentabilidade: foco na dimensão econômica - SOUSA FILHO, Pedro Rocha (2020)
ustainability is nowadays presented as an essential theme due to the evidence of the planet's limit. Thus, an economy based on growth due to increased consumption of natural resources is perhaps one of the main issues that aggravate global warming. That way, when planning indoor environments in the context of interior design, the professional in the area can assume an important educational role for an awareness of the use and reduction of consumption of natural resources and environmental impacts on nature. In addition, it is also capable of contributing to the promotion of local development in the design process for a more egalitarian economy; benefiting the economic dimension of sustainability through the practice of its principles. However, it is necessary to analyze the way that the professional understands and integrates such principles in his projects, aiming to guarantee his qualification for the valorization and defense of a fair and ethical economy. Therefore, this research aims to investigate the integration of the principles of the economic dimension of sustainability in the design process of interior designers. In this alignment, being of a qualitative nature and exploratory-descriptive characteristics, the methodological procedure adopted as a scope for collecting information the theoretical research, supported through the systematic bibliographic review, the application of an online questionnaire and the focus group technique. The data provided through the methodological triangulation allowed to gather an essential theoretical-practical basis for the synthesis of the study. As a conclusion of the research, it was possible to propose a set of 15 (fifteen) recommendations for the integration and operationalization of the principles of the economic dimension of sustainability in the design process of interior designers.